Prevalence and Molecular Characterization of Rickettsia spp. from Wild Small Mammals in Public Parks and Urban Areas of Bangkok Metropolitan, Thailand - Artharee Rungrojn; Kittipong Chaisiri; Yossapong Paladsing; Serge Morand; Jiraphan Junjhon; Stuart D. Blacksell; Peeraya Ekchariyawat (Tropical Medicine and Infectious Disease, 2021)
Rural areas usually show a higher prevalence of rickettsial infection than urban areas. However, information on the rickettsial infection status in urban settings (e.g., built-up areas and city parks) is still limited, particularly in the Bangkok metropolitan area. In this study, we performed a molecular rickettsial survey of spleen samples of small mammals caught in public parks and built-up areas of Bangkok. Out of 198 samples, the Rattus rattus complex was found to be most prevalent. The amplification of rickettsial gltA fragment gene (338 bp) by nested PCR assay revealed positive results in four samples, yielding a low prevalence of infection of 2.02%. DNA sequencing results confirmed that three samples were matched with Rickettsia typhi, and one was identified as R. felis. It is noteworthy that this is the first report of the occurrence of R. felis DNA in rodents in Southeast Asia.